Optimality conditions for infinite horizon control problems with state constraints - Oliveira, Valeriano Antunes de; Silva, Geraldo Nunes [UNESP] (Pergamon-Elsevier B.V. Ltd, 2009)
Necessary conditions of optimality in the form of a maximum principle are derived for state constrained optimal control problems with infinite horizon. A notable feature of our optimality conditions is the derivation of Michel's type transversality condition in the presence of state constraints. Under the usual interiority assumption for the vector field for large times, the strong transversality condition is also verified. (C) 2009 Elsevier Ltd. All rights reserved.
Keywords: Optimal control; State constraints; Infinite horizon problems; Optimality conditions